2020
DOI: 10.18203/issn.2455-4529.intjresdermatol20201582
|View full text |Cite
|
Sign up to set email alerts
|

Onychomadesis associated with hand, foot, and mouth disease: a prospective observational study from North Chennai

Abstract: Background: Hand, foot, and mouth disease (HFMD) is a common febrile illness caused by coxsackievirus A16 and human enterovirus 71 characterized by vesicular eruptions on hands and feet and enanthem on oral mucosa. Resolves usually without complications but onychomadesis can occur as a late sequlae sometimes. Methods: Children with clinical diagnosis of HFMD between April to June 2018 were included in the study. Age, sex, duration of illness, cutaneous features and nail changes were noted at initial visit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…[ 14 15 16 ] The combined review of other 48 publications/reports in the English-language literature which could be retrieved and considered relevant for clinicoepidemiological and virological features of HFMD are tabulated in Supplementary Table S1 . [ 12 13 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 ] Ten studies did not mention period of outbreak. Ten publications reported only single cases, 4 studies reported 2-5 cases and 34 were original or hospital based studies, and government reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 15 16 ] The combined review of other 48 publications/reports in the English-language literature which could be retrieved and considered relevant for clinicoepidemiological and virological features of HFMD are tabulated in Supplementary Table S1 . [ 12 13 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 ] Ten studies did not mention period of outbreak. Ten publications reported only single cases, 4 studies reported 2-5 cases and 34 were original or hospital based studies, and government reports.…”
Section: Resultsmentioning
confidence: 99%
“…[ 34 ] Delayed nail changes were also noted in 26.4% and 48.2% patients in two separate studies. [ 28 60 ] All cases had improved spontaneously requiring only symptomatic treatment and parental counselling. Relapses had occurred within 3-4 weeks and as late as 1-5 years.…”
Section: Resultsmentioning
confidence: 99%